Preventing the formation of deposits and energy losses in refrigeration installations by treating water supplying heat exchangers - Kaiser, Krzysztof; Marjanowski, Jan (Instal, 2024)
The article discusses the impact of deposits on the correct operation of heat exchangers and their impact on the energy aspect and operational losses associated with them. Attention was also paid to the need to periodically clean exchangers and ensure proper parameters of water used in cooling systems. The article also presents water treatment methods for refrigeration systems.
Keywords: heat exchanger; condenser; deposits and impurities; corrosion; energy losses